Development of Servant Leadership Training Modules to Improve The Performance of Educators and Educational Staff - Aktivia Ismi Lestari; Ferdy Semuel Rondonuwu; Yari Dwikurnaningsih (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to develop a Servant Leadership training module to improve the performance of educators and educational staff. The research employed the research and development (R&D) method using the Borg & Gall model, involving several stages from preliminary research, planning, draft development, initial field testing, and product revision, to implementation testing. Data collection was conducted through observations, interviews, questionnaires, pretests, and post-tests on a small-scale trial with six respondents and a large-scale trial with 30 respondents, including school principals, teachers, and educational staff in Central Lampung. The collected data were analyzed using descriptive analysis and statistical tests. This research resulted in a Servant Leadership training module designed to enhance the performance of educators and educational staff. Qualitative descriptive analysis indicated an urgent need for Servant Leadership training, while quantitative analysis demonstrated the effectiveness of the module, with a significant increase in pretest and post-test scores from 55.0 to 90.6. Expert validation confirmed the module's high feasibility, with a feasibility level of 92%. The main-scale trial also confirmed its feasibility with an 82.9% feasibility level, and the large-scale trial demonstrated a very high feasibility level of 91.2%. This module includes concept introduction, case studies, implementation strategies, reflection, and evaluation. The findings suggest that this module provides a practical solution for supporting the application of Servant Leadership principles and is expected to be effective in improving the performance of educators and educational staff.